Persepsi Masyarakat Dusun Iroyudan terhadap Pengembangan Pariwisata Taman Jati Larangan Kabupaten Bantul - Skolastika Widiatikasyanti; Elinda Tria Wati (Gemawisata: Jurnal Ilmiah Pariwisata, 2025)
Jati Larangan Park in Iroyudan Hamlet, Bantul Regency, is a community-based tourism area with historical, cultural, and natural potential. Despite its appeal as a religious and outdoor tourism destination, the park experienced a decline in activity following the COVID-19 pandemic. This study aims to analyze community perceptions of the development of Jati Larangan Park to support participatory and sustainable tourism development strategies. The research method used a qualitative descriptive approach with data collection techniques including in-depth interviews, observation, and documentation. The results indicate that the community has a positive perception of the park because it is considered capable of providing economic, social, and cultural benefits. Youth groups, MSMEs, and the general public recognize the importance of this tourism revival, although management is still hampered by human resources, weak institutional structures of the Tourism Awareness Group (Pokdarwis), and a lack of digital literacy for the promotion and marketing of local products. Community involvement is reflected in the spirit of mutual cooperation and the desire to revitalize the park through various tourism activities. However, a more systematic strategy is still needed in terms of institutional strengthening, youth empowerment, MSME capacity development, and digital promotion. With a Community-Based Tourism (CBT) approach, Jati Larangan Park has the potential to become a leading destination in Bantul with collaborative and sustainable management. In addition to social and economic aspects, the development of Jati Larangan Park must also consider environmental and spatial planning dimensions. Currently, parts of the park are poorly managed, with a lack of sanitation facilities, information boards, and accessible tourist routes for the elderly and people with disabilities. This presents a challenge in realizing an inclusive and comfortable destination.